Case characteristics, resource use, and outcomes of 10 021 patients with COVID-19 admitted to 920 German hospitals: an observational study - Karagiannidis, Christian; Mostert, Carina; Hentschker, Corinna; Voshaar, Thomas; Malzahn, Jürgen; Schillinger, Gerhard; Klauber, Jürgen; Janssens, Uwe; Marx, Gernot; Weber-Carstens, Steffen; Kluge, Stefan; Pfeifer, Michael; et al. (The lancet respiratory medicine, 2020)
Background Nationwide, unbiased, and unselected data of hospitalised patients with COVID-19 are scarce. Our aim was to provide a detailed account of case characteristics, resource use, and outcomes of hospitalised patients with COVID-19 in Germany, where the health-care system has not been overwhelmed by the pandemic. In this observational study, adult patients with a confirmed COVID-19 diagnosis, who were admitted to hospital in Germany between Feb 26 and April 19, 2020, and for whom a complete hospital course was available (ie, the patient was discharged or died in hospital) were included in the study cohort. Claims data from the German Local Health Care Funds were analysed. The data set included detailed information on patient characteristics, duration of hospital stay, type and duration of ventilation, and survival status. Patients with adjacent completed hospital stays were grouped into one case. Patients were grouped according to whether or not they had received any form of mechanical ventilation. To account for comorbidities, we used the Charlson comorbidity index. Of 10 021 hospitalised patients being treated in 920 different hospitals, 1727 (17%) received mechanical ventilation (of whom 422 [24%] were aged 18-59 years, 382 [22%] were aged 60-69 years, 535 [31%] were aged 70-79 years, and 388 [23%] were aged ≥80 years). The median age was 72 years (IQR 57-82). Men and women were equally represented in the non-ventilated group, whereas twice as many men than women were in the ventilated group. The likelihood of being ventilated was 12% for women (580 of 4822) and 22% for men (1147 of 5199). The most common comorbidities were hypertension (5575 [56%] of 10 021), diabetes (2791 [28%]), cardiac arrhythmia (2699 [27%]), renal failure (2287 [23%]), heart failure (1963 [20%]), and chronic pulmonary disease (1358 [14%]). Dialysis was required in 599 (6%) of all patients and in 469 (27%) of 1727 ventilated patients. The Charlson comorbidity index was 0 for 3237 (39%) of 8294 patients without ventilation, but only 374 (22%) of 1727 ventilated patients. The mean duration of ventilation was 13·5 days (SD 12·1). In-hospital mortality was 22% overall (2229 of 10 021), with wide variation between patients without ventilation (1323 [16%] of 8294) and with ventilation (906 [53%] of 1727; 65 [45%] of 145 for non-invasive ventilation only, 70 [50%] of 141 for non-invasive ventilation failure, and 696 [53%] of 1318 for invasive mechanical ventilation). In-hospital mortality in ventilated patients requiring dialysis was 73% (342 of 469). In-hospital mortality for patients with ventilation by age ranged from 28% (117 of 422) in patients aged 18-59 years to 72% (280 of 388) in patients aged 80 years or older. In the German health-care system, in which hospital capacities have not been overwhelmed by the COVID-19 pandemic, mortality has been high for patients receiving mechanical ventilation, particularly for patients aged 80 years or older and those requiring dialysis, and has been considerably lower for patients younger than 60 years. None.